THE DICTIONARY IS A MESSENGER OF TIME AND PERIOD (About the evolution of Uzbek dictionaries) (Scientific journal of the Fergana State University, 2024)
The article analyzes the periods of development of Uzbek lexicography, the process of improvement of dictionaries. Opinions about dictionaries from Mahmud Kashgari's "Devonu lugotit turk" to the current "Explanatory dictionary of the Uzbek language" are presented. The influence of the period on lexicography is emphasized. Recognizing that a number of scientific works have been carried out in Uzbek linguistics on the historical development of Uzbek lexicography, the evolution of dictionaries, and taking into account that this issue is the object of separate, special research, the articles published only in recent years are discussed. Conclusions are given, paying attention to the aspects related to time and period of the presented dictionaries. First of all, all the first dictionaries were bilingual (some of them were multilingual) and were created to translate foreign language words, proverbs and sayings, phrases into Turkish (Uzbek). Secondly, they are not large, the range of words obtained is made up of popular everyday words. Thirdly, due to the requirements of the time, many dictionaries were in handwritten form, and there were not many of them. Fourthly, the monolingual explanatory dictionary of the Uzbek language was not compiled until the last 20th-21st centuries. The first explanatory dictionary of the Uzbek language was created in the second half of the 20th century. All considered dictionaries can be recognized as a bright "mirror" of their time.